1977
DOI: 10.1111/j.1469-8137.1977.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

STOMATAL DEVELOPMENT AND SEASONAL CHANGES IN DIFFUSIVE RESISTANCE OF PRIMARY AND REGROWTH FOLIAGE OF RED OAK (QUERCUS RUBRA L.) AND RED MAPLE (ACER RUBRUM L.)

Abstract: SUMMARY From foliar emergence until senescence, the abaxial diffusive resistance of primary foliage, and of regrowth foliage produced after defoliation, was measured at several irradiances with a ventilated diffusion porometer. Concurrent measurements were made of stomatal dimensions and frequency, including scanning electron‐microscopy, and of leaf area. The diffusive resistance of newly emerged primary leaves was about 15 s cm−1 in maple and 20 s cm−1 in oak at all irradiances. The stomata became sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…Accordingly, many studies have suggested that changes in g s with leaf age are related to stomatal development, although few have directly related the two. Turner and Heichel (1977) observed that while diffusive resistance remained relatively constant, stomatal frequency first increased and then declined during leaf expansion in Quercus rubra L. and Acer rubrum L. Here, the decrease in stomatal frequency observed for young expanding leaves was counter to the progressive increase in g s . However, it should be noted that the total number of stomata per leaf remained fairly constant, and the number of mature stomata, with larger apertures, increased progressively, over the same period.…”
Section: Stomatal Conductancecontrasting
confidence: 45%
See 2 more Smart Citations
“…Accordingly, many studies have suggested that changes in g s with leaf age are related to stomatal development, although few have directly related the two. Turner and Heichel (1977) observed that while diffusive resistance remained relatively constant, stomatal frequency first increased and then declined during leaf expansion in Quercus rubra L. and Acer rubrum L. Here, the decrease in stomatal frequency observed for young expanding leaves was counter to the progressive increase in g s . However, it should be noted that the total number of stomata per leaf remained fairly constant, and the number of mature stomata, with larger apertures, increased progressively, over the same period.…”
Section: Stomatal Conductancecontrasting
confidence: 45%
“…3a). Turner and Heichel (1977) noted that although the highest stomatal conductance was measured when surfaces of developing leaves were covered by profuse epicuticular waxes, the onset of wax occlusion later in the season coincided with a decrease in g s for Acer rubrum. In contrast, g s of young expanding leaves of E. regnans continued to increase during expansion (Fig.…”
Section: Stomatal Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of g with age has been observed in many plants (e.g. tobacco: Vficlavik, 1974; broad-leaved trees: Turner and Heichel, 1977;bean: Minter, 1980;Pospis/lova and Sol~irovfi, 1984). The causal interpretation of this effect follows two lines.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic probably had more senescing leaves. It has been shown that r s is less sensitive to Qp when leaves approach senescence than in fully expanded green leaves (Turner & Heichel, 1977;Vos & Oyarzun, 1987).…”
Section: Resultsmentioning
confidence: 97%